2019
DOI: 10.1042/bsr20181660
|View full text |Cite
|
Sign up to set email alerts
|

The miRNA-608 rs4919510 G>C polymorphism confers reduce coronary injury of Kawasaki disease in a Southern Chinese population

Abstract: Kawasaki disease (KD) is also called mucocutaneous lymph node syndrome and is an acute febrile pediatric disease characterized by systemic vasculitis. KD typically occurs in children 5 years old or younger and occurs more often in males than in females. miRNA-608 has been reported to interact with interleukin-6 and affect innate immunity. The immune-mediated inflammation could induce the occurrence of KD; however, there is no previous research focused on the relationship between miRNA-608 polymorphism and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…31,32 We have previously reported that the CG/CC genotypes of the miRNA -608 rs4919510 polymorphism contribute to a higher occurrence of KD than the GG genotype. 33 ATP-binding cassette subfamily C member 4 ( ABCC4 ) rs7986087 T variant genotypes are also significantly associated with increased KD susceptibility, though the rs868853 T variant genotypes are associated with reduced KD susceptibility. 34 The angiotensinogen ( ATG ) polymorphism rs5050 significantly increases the risk of CAA in children with KD.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 We have previously reported that the CG/CC genotypes of the miRNA -608 rs4919510 polymorphism contribute to a higher occurrence of KD than the GG genotype. 33 ATP-binding cassette subfamily C member 4 ( ABCC4 ) rs7986087 T variant genotypes are also significantly associated with increased KD susceptibility, though the rs868853 T variant genotypes are associated with reduced KD susceptibility. 34 The angiotensinogen ( ATG ) polymorphism rs5050 significantly increases the risk of CAA in children with KD.…”
Section: Discussionmentioning
confidence: 99%
“…We genotyped SNP (lnc-ZNF33B-2:1 rs579501 was purchased from Applied Biosystems) from genomic DNA isolated from venous whole blood samples of sepsis patients and healthy controls. The DNA extraction and genotyping procedures have been published previously ( Wang et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our team previously found that the miR‐218 rs11134527 A>G polymorphism was not associated with KD risk, but it may have an age‐related relationship with KD susceptibility 15 . The miR‐608 rs4919510 G>C polymorphism may be a protective factor for coronary artery injury in KD 16 . Compared with carriers of the TT genotype, patients aged under 12 months who carried the miRNA‐13 rs1625579 TG/GG genotype showed a significantly higher risk of developing KD 17 .…”
Section: Introductionmentioning
confidence: 92%
“… 15 The miR‐608 rs4919510 G>C polymorphism may be a protective factor for coronary artery injury in KD. 16 Compared with carriers of the TT genotype, patients aged under 12 months who carried the miRNA‐13 rs1625579 TG/GG genotype showed a significantly higher risk of developing KD. 17 These results indicate that miRNA polymorphisms may play a key role in the pathogenesis and pathological process of KD.…”
Section: Introductionmentioning
confidence: 98%